Rapid Sequence Modification in the Highly Polymorphic Region (Hpr) of the Hemagglutinin Gene of the Infectious Salmon Anaemia Virus (Isav) Suggests Intra-Segmental Template Switching Recombination - Montoya-Kunsting, M; Vasquez-Martinez, y; Cortez-San Martin, M; Galleguillos-Becerra, C; Michelson-Quintana, S (Blackwell Publishing Ltd, 2020)
The ISAV has a genome composed of eight segments of (–)ssRNA, segment 6 codes for the hemagglutinin–esterase protein, and has the most variable region of the genome, the highly polymorphic region (HPR), which is unique among orthomyxoviruses. The HPR has been associated with virulence, infectivity and pathogenicity. The full length of the HPR is called HPR0 and the strain with this HPR is avirulent, in contrast to strains with deleted HPR that are virulent to varying degrees. The molecular mechanism that gives rise to the different HPRs remains unclear. Here, we studied in vitro the evolution of reassortant recombinant ISAV (rISAV) in Atlantic salmon head kidney (ASK) cells. To this end, we rescued and cultivated a set of rISAV with different segment 6-HPR genotypes using a reverse genetics system and then sequencing HPR regions of the viruses. Our results show rapid multiple recombination events in ISAV, with sequence insertions and deletions in the HPR, indicating a dynamic process. Inserted sequences can be found in four segments of the ISAV genome (segments 1, 5, 6, and 8). The results suggest intra-segmental heterologous recombination, probably by class I and class II template switching, similar to the proposed segment 5 recombination mechanism. © 2020 John Wiley & Sons Ltd